Subduction of the Mesoarchaean spreading ridge and related metamorphism, magmatism and deformation by the example of the Gridino eclogitized mafic dyke swarm, the Belomorian Eclogite Province, eastern Fennoscandian Shield. (January 2019) - Dokukina, Ksenia; Mints, Michael
Abstract: A model of Mesoarchaean spreading ridge subduction and related metamorphism, magmatism and deformation in an active continental margin is presented here. The eclogites exposed along northeastern boundary of the Belomorian orogen in the eastern Fennoscandian Shield were formed as a result of Mesoarchaean–Neoarchaean subduction and collision. The Belomorian eclogite province contains two eclogite associations have been recognized within TTG gneisses: (1) the subduction-type Salma association and (2) the Gridino mafic dykes. Protoliths of the Salma eclogites represent a sequence comprising oceanic layered gabbro, formed at ∼2.9 Ga in a slow-spreading ridge. The subduction began in a time span 2.9–2.87 Ga, and eclogite-facies events occurred between ca.2.87 and ca.2.78 Ga. Injection of a mafic magma into an active continental margin, recorded by the Gridino dyke swarm, is attributed to subduction of a mid-ocean ridge, commencing at 2.87 Ga. The dykes represent typical fissure intrusions and underwent metamorphism to eclogite, granulite and amphibolite facies. The dykes divide into two compositions (Fe-Ti gabbro and Mg-Cr gabbronorite) which represent alternating episodes of arc and slab window magmatism. The Fe-Ti gabbros have high Ti and low abundances of fluid-mobile and other LIL elements compared to HFSE and plot in the MORB and within-plate oceanic basalt fields. The Fe-Ti gabbros formed from low-degree of partial melting from a depleted mantle source. This petrogenesis is consistent with slab window model in which magmas were derived by decompression melting of suboceanic mantle that upwelled into the opening beneath continental margin following spreading ridge subduction. The Mg-Cr gabbronorites have low Ti along with high abundances of fluid-mobile elements and other LILE compared to HFSE and plot in arc basalt fields that imply melting of subduction-modified hydrous subcontinental mantle. As the mid-ocean spreading ridge entered a trench, continental rocks above subduction zone underwent deformations with pseudotachylyte-bearing strike-slip faults development that is an evidence of a fossile earthquake. Paleoseismic event was limited to crustal conditions above the brittle-ductile transition, corresponding to temperatures below 450 °C and depths above 15 km. The slab window opening induced upwelling of anhydrous mantle and formation of the Fe-Ti gabbro dykes. The Mg-Cr gabbronorite was formed at slab window edges from metasomatized mantle. Summarizing evidences, such as ophiolites, eclogite, arc magmatism, we suggest that the modern style of subduction and plate tectonics began already in Mezoarchaean time 2.9-2.8 Ga ago. Special aspect of the paper is an argumentation of Meso-Neoarchaean age of eclogite facies metamorphism in the Belomorian eclogite province.